A review of critical care nursing staffing, education and practice standards - Gill, Fenella; Leslie, Gavin; Grech, C.; Latour, J. (Elsevier Inc, 2012)
Summary: The aim of this paper is to review the differences and similarities in critical care nursing staffing, education and practice standards in the US, Canada, UK, New Zealand and Australia. Search methods: A university library discovery catalogue, Science Direct, Scopus databases and professional websites were searched. Key terms used included, critical care, specialist, standards, competency, practice, scope, workforce, staffing, ratios, qualifications, adverse events, and patient outcomes. The search was limited to articles that referred to critical care environments including paediatric and neonatal settings. Results: The database and hand search identified 40 relevant articles. Website searching resulted in a further 36 documents. A diversity of critical care nursing contexts and a lack of comparable workforce data made it difficult to quantify differences and similarities between countries. There is a general consensus about the importance of optimum staffing by registered nurses with a proportion of those holding relevant post-registration qualifications although there is no consistency in defining the educational preparation for a ‘qualified’ critical care nurse. Critical care nursing standards for the US, Canada, UK and New Zealand were predominantly developed by expert panels while the Australian standards were developed with a multi-methods study including observations of practice. All five standards documents were built upon national entry-to-practice nurse standards and contained similar constructs, although there was no construct common to all of the standards. Conclusion: There is a lack of evidence to support nursing staffing with post registration specialty qualifications. Existing standards are predominantly opinion based rather than supported by research. The expected standards for nursing practice are fundamentally similar.